Cranioplasty with polymethylmethacrylate prosthesis and 3D planification, case report and literature review - Jerez Robalino, James Philippe (2022)
In this aticle it is showns that it is possible to make a digital prosthesis with Polymethylmethacrylate (PMMA) with free programs and a low-cost and easy-to-use 3D printer. The clinical case corresponds to a 38-year-old male who reported having undergone emergency surgery for a subdural hematoma of traumatic origin, secondary to a fall from a 5-meter-high scaffolding, procedure done by the Neurosurgery Service with a decompressive craniotomy 10 months ago, nowadays he presents a bilateral defect at the supraorbital and frontal region, referring constant headaches and dizziness with a diagnosis of a trephination syndrome. We decided to digitally design a prosthesis with PMMA, placing it under balanced general anesthesia in the operating room through a coronal approach, fixing it with titanium screws and repositioning tissues with sutures. The visual defect was immediately eliminated, the symptoms disappeared completely, confirming it at the controls since day 7. It is shown that it is possible to perform a low-cost personalized cranial prosthesis in a simple way, solving the discomfort and eliminating the sequelae and complications that affect patients treated by decompressive craniectomies with the presence of defects.